In situ characterization of damage development in Cottonid due to quasi-static tensile loading - Scholz, Ronja; Delp, Alexander; Walther, Frank (Technische Universität Dortmund, 2020)
Cottonid is a layered material based 100% on cellulose that holds excellent material properties by being completely sustainable. The finite nature of petroleum-based resources nowadays makes these properties significant for technical applications again. To understand how Cottonid reacts to application-oriented mechanical loads and how it fails, development of microstructural damage on the surface and in the volume of Cottonid was studied using innovative in situ testing techniques for the first time. Quasi-static tensile tests were comparatively performed in a scanning electron microscope as well as a microfocus computer tomograph, and the development of defects present in the initial condition of the material was investigated. In the elastic region, no visible damage initiation on the surface and a decrease of overall void volume within the gauge length could be detected. When reaching the yield strength, crack initiation on the surface starts at critical areas, like pores and microcracks, which propagation and assembly could be visualized via scanning electron micrographs. In the plastic region, an increase in void volume could be shown in the gauge length until final failure of the specimen. Innovative material testing techniques presented in this study support lifetime estimation in technical applications and understanding of process–structure–property relations. Particularly, characterization of microstructural damage development due to a mechanical load, which leads to final failure of the specimen, is essential to be able to create material models for lifetime prediction in respect to variable manufacturing or application parameters.
Materials;13(9)
Keywords: Cottonid; Cellulose; In situ testing; Scanning electron microscope; Microfocus computer tomograph; Quasi-static loading; Microstructure; Damage development; Damage mechanisms; Crack initiation; 660; Vulkanfiber; Cellulose; In situ; Rasterelektronenmikroskop; Mikrocomputertomographie; Zugversuch; Mikrostruktur; Werkstoffschädigung; Rissbildung